Recycling e-waste into gold-loaded covalent organic framework catalysts for terminal alkyne carboxylation - Amin Zadehnazari; Florian Auras; Ataf Ali Altaf; Amin Zarei; Ahmadreza Khosropour; Saeed Amirjalayer; Alireza Abbaspourrad (Nature Communications)
Abstract The rising demand for gold requires innovative methods for its recovery from e-waste. Here we present the synthesis of two tetrazine-based vinyl-linked covalent organic frameworks: TTF-COF and TPE-COF that adsorb gold ions and nanoparticles and catalyze the carboxylation of terminal alkynes. These covalent organic frameworks have low band gaps and high photocurrent responses. TTF-COF has an adsorption capacity toward aqueous Au(III) of 2440 mg g–1, and TPE-COF’s Au(III) adsorption capacity is 1639 mg g–1. The gold source is metal flakes isolated from waste computer processing units. Of the gold present, > 99% is selectively captured by TTF-COF whereas only 5% of the Ni and 2% of the Cu in the solution is adsorbed. The Au-loaded covalent organic frameworks catalyze the carboxylation of terminal alkynes and are stable and reusable for six reuse cycles. Our covalent organic frameworks convert e-waste into a valuable catalyst for a useful green organic transformation.